An umbrella review of physical-activity therapy and cognitive behavioral therapy in reducing fear of falling among community-dwelling older adults: insights on intervention intensity and duration - Yuan Sheng; Caili Wang; Yan Wang; LunPing Pan; Mengmeng Zhang; Deshan Liu; Wei Gao (Frontiers in Public Health)
IntroductionData about the impact of varying physical-activity therapy (PAT) intensities and the ideal duration of cognitive behavioral therapy (CBT) on older adults is inadequate. In this umbrella review, we seek to comprehensively synthesize and analyze findings from systematic reviews and meta-analyses regarding the optimal PAT intensity for lowering FOF and the duration of CBT interventions for effectively lowering FOF.MethodsThe PubMed, Web of Science, Cochrane Library, Medline, Embase, and CINAHL databases were searched up to April 2024. AMSTAR 2 was applied to assess the methodological and reporting quality. The quality of evidence for each intervention’s effect was evaluated using GRADE guidelines. A further meta-analysis of the primary studies was conducted to evaluate the effects of PAT intensity and CBT duration.ResultsIn the 18 included studies, 12 were PAT interventions, 3 were multifactorial, and 3 were CBT interventions. The umbrella review found that PAT and CBT interventions can effectively manage FOF. Comparable improvements were reported with low- and moderate-intensity PAT intervention (p < 0.0001); Significant improvements were observed with CBT immediately post-intervention, in the short-term (<6 months), and in the long-term (≥6 months) (p < 0.0001).DiscussionOur study revealed that a comprehensive intervention strategy combining low or moderate PAT with CBT interventions is more effective than isolated approaches, as it addresses the multifaceted nature of fear and fall risk. Future research should continue to track the long-term effects of synergistic interventions to optimize fall prevention strategies for older populations.Systematic review registrationhttps://www.crd.york.ac.uk/prospero Identifier CRD42024557893.